Analysis of Mathematical Representation Process Standard in Learning Mathematics on Relation Material - Fashihah Fashihah; Abd Qohar (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2020)
Representation is the interpretation of students' thinking to a problem in the form of words or verbal, text, tables, graphs, or symbols of mathematics as an aid instrument to solve problems. Representation is an important process standard in mathematics learning. There are 3 representation process standards in learning. One of the materials that requires the ability of representation at junior high school level is relation. This study aimed at describing the mathematical representation process standard in learning mathematics in relation material. This study used a qualitative approach to the type of descriptive research. The research procedures in this article were (1) designing learning instruments, (2) implementing learning design in peer teaching, (3) conducting learning analysis related to the abilities. The results of the study showed that the first process standard was seen in apperception activity, Activity 1 on LKS (student worksheet), Activity 2 on LKS (student worksheet), group presentations, and exercises. The second process standard was seen prominently in the exercise activities, while the third process standard was seen prominently in Activity 2 on LKS (student worksheet). Based on the results of the study, it can be concluded that the three process standards have been seen in almost all learning activities